Diagnóstico de la industria maderera en Veracruz - Ruelas Monjardín, Laura C.; Chávez Cortes, Juan M. (Instituto de Ecología, A.C., 2016)
An analysis about the status of the wood industry in the state of Veracruz, México is done, simultaneously, it is assessed that established in the states of Puebla, México, Tlaxcala and Hidalgo. For the objectives of this paper, these states are considered to be grouped in the mid-west region. Also, to outline the situation of Veracruz in the national context, it is compared with the most important states regarding wood production, which are: Durango, Chihuahua and Michoacán. The relationship with the midwest region is that, because of geographical reasons, the region becomes the natural market for Veracruz forest products. The analysis was based in a survey applied by the Secretary of the Environment, Natural Resources and Fisheries, to the national forest industry, during September-December 1995. This diagnostic includes: number of industries, municipalities in which they are located, type of ownership, industrial capacity and its current state of use and type of industry. The industry potential is assessed, taking into account the forest land and the volume that could be exploited per state and for the region. For the state of Veracruz the level of wood prices are given, comparing them with the national average, and taking into account the sale point: standing, in the road and in the yard. Survey’s results point out that, the sawing industry prevails; the average industry works at 39% of its capacity. Since the 50's, wood industry production in Veracruz has been falling and its industrial capacity is underutilized. The situation could be partially explained by the conversion of forestlands to agricultural uses, mainly for cattle ranching.